Synthesis and characterization of telechelic hydroxyl functional poly (N-vinylpyrrolidone) - Pfukwa, Rueben (Stellenbosch : Stellenbosch University, 2008)
Thesis (MSc (Chemistry and Polymer Science))--Stellenbosch University, 2008.